Analysis of the Reasons for the success of Douyin- Based on the perspective of user value co-creation - Tan, Xiaolin (Pacific International Journal, 2023)
In the new media era, short video has become the main channel for users to engage in social entertainment and obtain consultation. Douyin, as a leader in the field of short videos, attracts huge traffic. Taking Douyin as the research object, based on the perspective of user value co-creation, this paper analyzes the impetus of the platform for user value co-creation from two aspects of content creators and content viewers. And summarize the experience and inspiration, in order to provide valuable and meaningful reference for the development and brand promotion of other apps.